Metabolit Sekunder dan Aktivitas Antibakteri Ekstrak Metanol Daun Kamboja Putih (Plumeria acuminata Ait) Terhadap Beberapa Bakteri Uji - Farid, Riza; Fitriani, Victoria Yulita; Ibrahim, Arsyik (Jurnal Riseta Naturafarm, 2024)
Kamboja (Plumeria acuminata Ait) plant is traditional medicine used as medication for ulcer and abscess. Steroid and tanin is component of chemical compound in kamboja leaves that supposed to have antibacterial activity. This study aims to determine the content of secondary metabolites and effective concentration of methanol extracts of kamboja leaves as antibacterial. Identification contains of secondary metabolites by used reagent Mayer, Dragendorf, Liebermann-Burchard, FeCl, Mg powder and HCl. Analysis of secondary metabolites characterized by the presence of sediment or froth. The antibacterial activity test carried out by agar diffusion method. Inhibition zone is analyzed by Anava and Duncan test. Secondary metabolite the compound containing steroid and tanin. The effective concentration of 40% were significantly different with a value of p = 0.00 (p<0.05) on the growth of Streptococcus mutans and Staphylococcus aureus bacteria and a concentration of 30% is very significantly different from the value of p = 0.00 (p<0.05) on the growth of Escherichia coli bacteria in vitro.